Analisis Waste dalam Aliran Material Internal dengan Value Stream Mapping Pada PT XYZ - Ayu, Gita; Hanggara, Jeffry; Kurniawan, David; Gunawan, Gunawan (Bina Nusantara University, 2012)
The main focus of the research is excess inventory and motion waste which commonly occur in warehouse and production floor. This research is carried out to minimize the average level and eliminate unnecessary motions, with consideration of electronic pull and traceability system characteristics. Product X, the highest-selling product, is the object of this research. To identify the current condition, the current state Value Stream Mapping (VSM) is developed as the basis to arrange improvement plan to minimize the wastes. Safety stock is determined through average and maximum consumption difference; and reorder point is determined to comply with pull approach. Average inventory level is calculated using continuous review method. The simulation was conducted and it was shown that 8.29 minutes is the maximum lateness. Thus, safety stock and reorder point are adjusted accordingly to anticipate stockout due to lateness. The improvement of process cycle efficiency is shown to increase from 4.1 % to 5.1 % as projected in future state VSM.